Associação entre saúde bucal e o risco de sarcopenia em pacientes doentes renais crônicos submetidos à hemodiálise - Cardoso, Kailane Martins (2022)
Background: Poor oral health and sarcopenia are very prevalent among renal patients. We aimed to verify the association between oral health and risk of sarcopenia in chronic kidney disease (CKD) patients submitted to HD. Methods: The sample was formed by 147 CKD patients undergoing HD in October 2020 at a single dialysis center. Demographic and clinical data were collected. Oral health was assessed by oral examination. Oral hygiene habits were checked by the application of a questionnaire. Risk of sarcopenia was classified using the SARC -F questionnaire. Comparisons were performed between patients with and without risk of sarcopenia. Multivariate logistic regression was carried out to determine independent predictors of risk of sarcopenia. Results: There were 62 (42.2%) patients classified as having risk of sarcopenia. Less than 20% had the habit of dental flossing, only 32.8% reported performing 3 tooth brushings per day, and almost half of patients had more than 20 missing teeth. In the comparison between patients with and without risk of sarcopenia, there was higher prevalence of risk of sarcopenia among patients with more missing teeth, using prostheses, with alteration in oral mucosa, and with lower number of daily dental brushings. In the multivariate analysis, only higher grade of comorbidities was an independent predictor of risk of sarcopenia (OR=1.902; CI=1.125 -3.285). Conclusions: There was lack of oral hygiene habits and a very high prevalence of poor oral health and risk of sarcopenia. There was no association between oral health and risk of sarcopenia. Higher grade of comorbidities predicted higher risk of sarcopenia.